Analisis Faktor yang Mempengaruhi Nilai Ekspor Teh Sumatera Utara - Qamarani, Jasmine; Qalsum, Ummy; Santri, Linda (Jurnal Agrisep, 2025)
Tea is a significant commodity in generating foreign exchange through exports. Indonesia has large amount of potential to enhance the quality and quantity of tea production, being one of the world's largest tea exporters. The most of tea production in North Sumatra is intended for export. However, the export volume of North Sumatra tea tends to decline annually. This study aims to analyze the influence of production, GDP, population, and the exchange rate of the US dollar on the competitiveness of North Sumatra tea exports. The method used to analyze the data is panel regression using the Fixed Effects model. The estimation results indicate that if North Sumatra tea production, the GDP of export destination countries, the population of export destination countries, and the exchange rate of the destination countries' currencies against the US dollar are held constant, the export value will decrease by -27.96364.